Selected measures for managing subsidised drug use in the Pharmaceutical Benefits Scheme : Department of Health and Ageing - Australian National Audit Office; Nicoll, Paul.; Jackson, Deborah; Donaldson, Andrea (Canberra : Australian National Audit Office, 2006)
The objective of the audit was to examine how effectively Health manages the risk of PBS drugs not being used according to PBS subsidy conditions.
"Audit Team: Paul Nicoll, Deborah Jackson, Andrea Donaldson"--P. 4.
Includes bibliographical references.
Also available in an electronic version on the Internet. Address as at July 18, 2006: ttp://www.anao.gov.au/WebSite.nsf/Publications/7B24934A2DE1C8DDCA25717E0082E5E2
Also available online
Keywords: Pharmaceutical Benefits Scheme (Australia) -- Auditing; Australia. -- Dept. of Health and Ageing -- Auditing; Pharmaceutical services -- Australia -- Auditing